Manusia Sebagai Pelaku Sejarah (Studi Kasus: Peran Mahasiswa dalam Runtuhnya Orde Baru) - Dedy Firman Maulana; Firda Aulia; Ika Nafiani; Kartika Kurnia Eka W.; Hany Nurpratiwi (Populer: Jurnal Penelitian Mahasiswa, 2023)
The struggles of the student movement in Indonesia can be seen from its history which was influenced by changes in the ruling regime and pilot-economic order. The role of students in the dynamics of power change in Indonesia has a considerable influence, such as during the fall of President Soeharto which gave birth to the New Order era. The purpose of this study is to discuss more deeply the role of the student movement in resisting the New Order. In this study using the literature study method by collecting research data through relevant books, journals, and previous articles. The results obtained from this study are that the struggles of the student movement experienced a dynamic development, this clearly illustrates that the movement carried out by students during the New Order era played an important role in turning the wheels of history.